Doing the Same and Earning Less: Male and Female Physicians in a New Medical Specialty - Timothy J. Hoff (SAGE Publishing, 2004)
This study presents findings from a national survey of physicians working in the emerging career of hospital medicine. It finds that female hospitalists earn significantly less annually than male hospitalists, despite similar work schedules and commitments; that these similarities in work and differences in pay remain even for male and female hospitalists who are married and have children; and that female hospitalists maintain positive feelings toward their work careers despite assuming multiple work and nonwork roles simultaneously. The results present a unique picture of female physicians career experiences in toto. They have implications for how health care organizations and managers should think about the contemporary female physician (e.g., her career development needs and workplace challenges); for female physicians need to gain greater equity vis-à-vis men within the profession; and for the kinds of questions researchers should raise around physician gender in their work.